Aniline and indoline donors based far-red active unsymmetrical squaraine dyes for dye sensitized solar cells - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Chemphotochem, 2024)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on the metal-oxide surface by appending the alkyl groups around the donor or pi-spacer unit of the dye is a potential approach to enhance DSSC efficiency. Further, rigidification of the dye structures by cyclization modulates the photophysical properties of the sensitizer. Here a series of donor-acceptor-donor (D-A-D) type far-red active unsymmetrical squaraine dyes (SQA) have been designed and synthesized, where N,N-dimethylaniline, methylated- and branched-indoline have been used as donor units. These dyes showed absorption between 629-654 nm (lambda max) with the molar extinction coefficient of 1.49-1.94x105 M-1 cm-1. Systematic enhancements in DSSC device efficiency have been observed due to the cyclization and alkyl-groups incorporation in this set of dyes which were further enhanced with the addition of chenodeoxycholic acid (CDCA). The highest DSSC device efficiency of 4.78 % (Jsc of 8.77 mA/cm2 and Voc of 692 mV) has been achieved for SQA3. The IPCE profile of SQA dyes indicates the contribution of aggregated structures for the photocurrent generation. Further, co-sensitization of SQA3 dye with a complementary visible light active dye AK4 showed the enhanced device efficiency of 6.27 % with panchromatic IPCE response. Dye rigidification, and controlled aggregation of dyes on TiO2 by means of cyclization of donor unit and introducing the alkyl groups in the dye structure synergistically improve the dye-sensitized solar cell (DSSC) device performance. Donor-Acceptor-Donor (D-A-D) based unsymmetrical squaraine dye SQA3 showed the DSSC device performance of 4.78 %.image
Keywords: co-sensitization; dye-sensitized solar cell; effect of alkyl chain; molecular planarity; squaraine dye

Far-red active squaraine dye-sensitized photoanode for dye-sensitized solar cells with a copper (II/I) electrolyte - Nawghare, Indrajeet S.; Deshmukh, Shivdeep Suresh; Joshi, Krati; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of Photochemistry and Photobiology A-Chemistry, 2025)
In dye-sensitized solar cells (DSSC), controlling the dye-aggregation on TiO2 and charge recombination between electrons present in TiO2 and electrolyte can be achieved by wrapping the long alkyl groups around the dye structure and further introducing bulky donor on the dye is a potential approach to enhance both the open-circuit potential and short-circuit current parameters. Additionally, bulky donor containing dye structures modulates the photophysical and electrochemical properties of the sensitizer which helps reducing the over potentials required for the dye regeneration process by utilizing a multidentate ligand containing [Cu(tme)]2+/+ and I- /I3redox electrolytes. Hagfeldt donor appended far-red NIR active unsymmetrical squaraine dye (SQ-HF) has been designed, synthesized, and characterized. SQ-HF dye showed an intense absorption at 676 nm (epsilon 1.7 x 105 M- 1cm- 1). Photophysical and electrochemical studies indicated that the LUMO and HOMO energy levels of the SQ-HF dye were suited for charge injection (from the LUMO of the dye to the conduction band of TiO2) and dyeregeneration processes, respectively. The DSSC device efficiency of 5.15 % (JSC of 10.83 mA/cm2 and VOC of 0.690 V) has been achieved for SQ-HF dye by utilizing a literature reported [Cu(tme)]2+/+ and 4.11 % (JSC of 8.74 mA/cm2 and VOC of 0.702 V) in I- /I3- redox shuttles, respectively.
Keywords: aggregation of dyes; Bulky donor; dye-sensitized solar cell; Photocurrent generation; squaraine dye